Gate voltage-dependent magnetoresistance of Zn0.8Co0.2O:H. Issue 100 (12th October 2016) - Cheon, Miyeon; Cho, Yong Chan; Cho, Chae-Ryong; Park, Chul Hong; Jeong, Se-Young
Abstract : The magnetoresistance (MR) of ZnCoO:H was measured at 7 K to verify the MR dependency on carrier density. It was found that MR increased with negative gate voltage. This increase in MR is not caused by an increase in pMR, but by a decrease in nMR. Abstract : The magnetoresistance of a hydrogenated Zn0.8 Co0.2 O film with an inverted thin film transistor structure was measured at 7 K, in magnetic fields up to 3 T in order to verify the magnetoresistance dependency on carrier density. The gate voltage-dependent magnetoresistance was measured between −15 V and 15 V. A large positive magnetoresistance was identified at all gate biases. Changes in positive gate voltage did not result in significant changes in the magnetoresistance; however, an increase in negative gate voltage resulted in an increase in magnetoresistance and zero field resistivity. The magnetoresistance comprises a positive component, as a result of quantum conductivity correction due to the s–d exchange interaction, and a negative component induced by weak localization. The gate voltage-dependence of the positive and negative magnetoresistances was described by the density of states for ZnCoO:H.